Molecular typing of Streptococcus pyogenes from remote Aboriginal communities where rheumatic fever is common and pyoderma is the predominant streptococcal infection - McDONALD, M. I. (Cambridge University Press, 2007)
Aboriginal Australians in remote communities have high rates of rheumatic heart disease (RHD); yet pharyngitis is reportedly rare whilst pyoderma is common. Some strains of group A streptococci (GAS) have preference for the throat and others for the skin depending on M protein type. A study in three remote communities provided 350 GAS isolates for emm sequence typing, 244 were also emm pattern typed. There was 100% correlation between emm sequence and pattern type. Patterns D and E (non-throat tropic) made up 71% of throat and 87% of skin isolates although patterns A–C (throat tropic) were more common in the throat than the skin (RR 2·3, 95% CI 1·4–3·8) whilst the opposite was found for pattern D (RR 2·2, 95% CI 1·7–3·0). Pattern E favoured the throat (RR 1·4, 95% CI 1·1–1·8). Where environmental factors predispose to skin infection, emm pattern types D and E prevail, whatever the recovery site.